Structured Feature-Based Component Architecture Design from a Traceability Perspective - Yoo, Insun; Ryu, Ki Yeol (International Conference on Ubiquitous and Future Networks, ICUFN, 2024)
Embedded software requires high reliability and safety. From the perspective of embedded software development, a component-based architecture promotes software reusability. To enhance the reliability, safety, and reusability of embedded software, tracking of components is crucial. In this study, we analyze the component-based software architecture design process, based on existing structured features, from the perspective of requirement traceability. We express the design method through a meta-model and conduct analysis by tracking the outputs at each stage of the process.
Keywords: Architecture designs; Component architectures; Component-based architecture; Component-based software architecture; Design-process; Embedded software development; Feature-based; High reliability and safeties; Software architecture design; Structured feature; component-based software architecture; embedded software; structured feature